Computational biomechanical analysis of postoperative inferior tibiofibular syndesmosis: a modified modeling method. Issue 5 (4th April 2018) - Li, Haobo; Chen, Yanxi; Qiang, Minfei; Zhang, Kun; Jiang, Yuchen; Zhang, Yijie; Jia, Xiaoyang
Abstract: To analyze the biomechanical effect of syndesmotic screw through three and four cortices, a total of 12 finite element models simulating healthy ankles, tibiofibular syndesmosis injured ankles, and post-operative ankles by screw fixations through three or four cortices were built. A set of biomechanical data were obtained to find that screw fixation methods for inferior tibiofibular syndesmosis can help recover most of the biomechanical relations of the ankle especially the tricortical fixation, while the screw of quadricortical fixation bear more stress than the tricortical fixation. The modeling method for finite element models was also modified for saving more time and realizing personalized modeling for clinical application.